Impact of Overnight Storage of Human Atrial Myocytes on Intracellular Calcium Homeostasis and Electrophysiological Utility - Cristina Aceituno; David Revuelta; Verónica Jiménez-Sábado; Antonino Ginel; Cristina E. Molina; Leif Hove-Madsen (Biomolecules)
Human atrial myocytes afford an attractive experimental model to investigate mechanisms underlying electrophysiological alterations in cardiovascular disease. However, this model presents limitations, such as the availability of human atrial tissue and a variable yield of myocytes isolation. Therefore, we aimed to determine whether overnight storage can increase the time window where the electrophysiological properties of human atrial myocytes can be determined. To address this issue, human atrial myocytes isolated from patients undergoing cardiac surgery were used for patch-clamp experiments on the day of cell isolation (Day 1) and the following day (Day 2). The shape of the current–voltage (I–V) relationship for the calcium current (ICa) depended on the access resistance and the cell capacitance, with large cells (>75 pF) requiring a lower access resistance (<15 MΩ) than small cells (<40 pF) to avoid distortion of the I–V curve. Importantly, overnight storage did not significantly affect (1) the ICa amplitude or properties, (2) sarcoplasmic reticulum calcium homeostasis or (3) the frequency-dependency of the beat-to-beat response. In conclusion, overnight storage of isolated human atrial myocytes at 4 °C does not affect essential features of intracellular calcium homeostasis and, therefore, affords a simple protocol to extend the experimental lifetime of human atrial myocytes.